Menumbuh Kembangkan Motivasi Menulis Siswa SD Dengan Mading (Studi Kasus di Desa Karya Jadi) - Alfin Siregar; Chusnul Hidayati; Lailan Maharani; Nada Afifah; Nurul Liza (Jurnal Ilmiah Wahana Pendidikan, 2023)
The motivation to learn to write in elementary school students can be a determinant of students' ability to improve the writing skills of elementary school students. This study uses magazines because magazines are one of the attractions for children's attention. The purpose of this research is to increase the motivation to learn to write with madding in elementary school students. This research uses a qualitative method. Qualitative research is research that presents data with descriptions. Data collection technique is done by observation method. This type of research is field research. Data analysis consists of three components, namely data reduction, data presentation and conclusion. Based on the research results, the implementation of developing students' writing motivation is integrated into school activities, namely habituation activities.